Alat Keamanan Depan Rumah Berbasis Internet of Things (IoT) Menggunakan ESP32-CAM yang Terintegrasi dengan Face Detection dan Telegram - Saputra, Christian Ferry Masyu; Sulistyo, Wiwin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Crimes that happen cannot be avoided when and how they will occur, as well as when at home. When the empty state is left away or when the occupants of the house are resting, usually many people do not realize and may not even know how to avoid mistakes when driving to maintain distance in order to avoid collisions and prevent crimes that can harm the occupants of the house both physically and materially. Based on the problems that occur, it is necessary to solve the problem in order to minimize the crime that occurs by making an Internet Of Thing-based home security tool using ESP32Cam and Telegram. The code application used in designing home security tools in this study is to use the Arduino IDE. Later the design tool in this study will use a Face Deection system that functions to detect faces which can later be very useful, which can detect faces in the home area in real-time as a warning sign through the telegram application whenever and wherever the home owner is as long as there is a gadget